2005
DOI: 10.1002/lt.20394
|View full text |Cite
|
Sign up to set email alerts
|

Initial hepatic microcirculation correlates with early graft function in human orthotopic liver transplantation

Abstract: Microcirculatory disturbances are an initial causative determinant in hepatic ischemia/reperfusion injury. The aim of this study was to assess sinusoidal perfusion during human liver transplantation using orthogonal polarization spectral imaging and to evaluate the significance of intraoperative microcirculation for early postoperative graft function. Hepatic microcirculation was measured in 27 recipients undergoing full-size liver transplantation and compared to a group of 32 healthy living-related liver dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…The development of subcutaneous and trocar site metastases and immunologic defense mechanisms of the tumor host are some examples of hotly debated topics of laparoscopic surgery that come across the entity of IRI with common intermediary cytokines [69,70,74]. If such an effect of pneumoperitoneum is confirmed in humans using an appropriate setting such as orthogonal polarization spectral imaging [75], the application of hepatoprotective agents or ischemic preconditioning [76,77] might be important for laparoscopic surgery to minimize the potential adverse effects of reperfusion injury to liver. …”
Section: Conclusion and Clinical Applicationmentioning
confidence: 98%
“…The development of subcutaneous and trocar site metastases and immunologic defense mechanisms of the tumor host are some examples of hotly debated topics of laparoscopic surgery that come across the entity of IRI with common intermediary cytokines [69,70,74]. If such an effect of pneumoperitoneum is confirmed in humans using an appropriate setting such as orthogonal polarization spectral imaging [75], the application of hepatoprotective agents or ischemic preconditioning [76,77] might be important for laparoscopic surgery to minimize the potential adverse effects of reperfusion injury to liver. …”
Section: Conclusion and Clinical Applicationmentioning
confidence: 98%
“…Transaminase activity levels represent a well-established parameter for the estimation of hepatic injury after OLT, and some studies have implicated AST as a determinant of higher patient mortality. 17,18 However, AST levels alone were not found to be predictive of the occurrence of EAD. 16 Rosen et al 18 demonstrated that patient survival is not influenced by ischemia-reperfusion injury up to an AST of 5,000 U/L, and that an equal proportion of grafts exhibiting severe ischemia reperfusion injury with AST Ͼ5,000 U/L provide longterm function as are lost to primary nonfunction.…”
Section: Discussionmentioning
confidence: 91%
“…Each patient received 1 to 6 MARS treatments lasting for a median of 16 (14)(15)(16)(17)(18)(19) hours. The combination of serum bilirubin Ͼ10 mg/dL, PDR ICG Ͻ10% per minute, AST/ALT Ͼ1,000 U/L, and PT Ͻ40% was present in 4 patients.…”
Section: Resultsmentioning
confidence: 99%
“…As the correlation between the pathophysiology of hepatic microcirculation and ischemia/reperfusion injury has been demonstrated, intraoperative analysis if ischemia/reperfusion-induced impairment of hepatic microcirculation has gained interest. Orthogonal polarization spectral imaging has been used accurately for this purpose; quantifying the sinusoidal perfusion rate, vessel diameter and venular RBC velocity (Puhl et al, 2005).…”
Section: Future Directions For Circulatory Monitoringmentioning
confidence: 99%